Effects of Neurodevelopmental Therapy on Gross Motor Function in Children with Cerebral Palsy - LABAF, Sina; SHAMSODDINI, Alireza; HOLLISAZ, Mohammad Taghi; SOBHANI, Vahid Sobhani; SHAKIBAEE, Abolfazl (Iranian Journal of Child Neurology, 2015)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--> How to Cite This Article: labaf S, Shamsoddini A, Hollisaz MT, Sobhani V, Shakibaee A . Effects of Neurodevelopmental Therapy on Gross Motor Function in Children with Cerebral Palsy. Iran J Child Neurol. Spring 2015;9(1):37-42. Abstract Objective Neurodevelopmental treatments are an advanced therapeutic approach practiced by experienced occupational therapists for the rehabilitation of children with cerebral palsy. The primary challenge in children with cerebral palsy is gross motor dysfunction. We studied the effects of neurodevelopmental therapy on gross motor function in children with cerebral palsy. Materials & Methods In a quasi-experimental design, 28 children with cerebral palsy were randomly divided into two groups. Neurodevelopmental therapy was given to a first group (n=15) with a mean age of 4.9 years; and a second group with a mean age 4.4 years (n=13) who were the control group. All children were evaluated with the Gross Motor Function Measure. Treatments were scheduled for three - one-hour sessions per week for 3 months. Results We obtained statistically significant differences in the values between the baseline and post treatment in two groups. The groups were significantly different in laying and rolling (P=0.000), sitting (0.002), crawling and kneeling (0.004), and standing abilities (P=0.005). However, there were no significant differences in walking, running, and jumping abilities between the two groups (0.090). Conclusion We concluded that the neurodevelopmental treatment improved gross motor function in children with cerebral palsy in four dimensions (laying and rolling, sitting, crawling and kneeling, and standing). However, walking, running, and jumping did not improve significantly. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->